Detection of selective sweeps in structured populations: a comparison of recent methods. Issue 1 (12th October 2015) - Vatsiou, Alexandra I.; Bazin, Eric; Gaggiotti, Oscar E.
Abstract: Identifying genomic regions targeted by positive selection has been a long‐standing interest of evolutionary biologists. This objective was difficult to achieve until the recent emergence of next‐generation sequencing, which is fostering the development of large‐scale catalogues of genetic variation for increasing number of species. Several statistical methods have been recently developed to analyse these rich data sets, but there is still a poor understanding of the conditions under which these methods produce reliable results. This study aims at filling this gap by assessing the performance of genome‐scan methods that consider explicitly the physical linkage among SNPs surrounding a selected variant. Our study compares the performance of seven recent methods for the detection of selective sweeps (iHS, nSL, EHHST, xp‐EHH, XP‐EHHST, XPCLR and hapFLK). We use an individual‐based simulation approach to investigate the power and accuracy of these methods under a wide range of population models under both hard and soft sweeps. Our results indicate that XPCLR and hapFLK perform best and can detect soft sweeps under simple population structure scenarios if migration rate is low. All methods perform poorly with moderate‐to‐high migration rates, or with weak selection and very poorly under a hierarchical population structure. Finally, no single method is able to detect both starting and nearly completed selective sweeps. However, combining several methods (XPCLR or hapFLK with iHS or nSL) can greatly increase the power to pinpoint the selected region.